Pengaruh Literasi Keuangan Dan Penyuluhan Terhadap Akses Kredit Mikro Formal Petani Sayuran - Syafira Syafa’at, Iin Aulia; Nidar, Sulaeman Rahman (Universitas Pakuan, 2025)
THE INFLUENCE OF FINANCIAL LITERACY AND EXTENSION PARTICIPATION ON FORMAL MICROCREDIT ACCESS AMONG VEGETABLE FARMERSThis study analyzes the influence of financial literacy and extension participation on access to formal microcredit among vegetable farmers in Cikidang Village, West Bandung Regency. Access to financing remains a major challenge for small-scale farmers in Indonesia, largely due to low financial literacy, limited knowledge of financing products, and minimal interaction with formal financial institutions. These conditions often reduce farmers’ confidence in applying for credit and hinder their ability to meet administrative requirements set by lenders. The research employed a quantitative method using questionnaires distributed to 127 farmers and logistic regression analysis. The findings indicate that both financial literacy and extension participation have a positive and significant effect on access to formal microcredit. The regression model explains 57.9% of the variation in credit access. A one-unit increase in financial literacy raises the likelihood of obtaining credit by 2.15 times, while participation in extension activities increases the likelihood by up to 29.76 times. These results emphasize that farmers with stronger financial understanding are better equipped to recognize the benefits of credit, manage risks, and complete required documentation. Likewise, extension activities enhance farmers’ knowledge of credit procedures, application steps, and strategies for using loans productively. Overall, improving financial literacy and strengthening extension participation are essential measures to enhance farmers’ access to formal microcredit services and support sustainable agricultural development.